Midwifery Care for Postpartum Mothers With After Pains Discomfort in Maternity Hospital: Asuhan Kebidanan pada Ibu Nifas Dengan Ketidaknyamanan After Pains di Rumah Sakit Bersalin - Islamiah, Nur Intan; Hanum, Sri Mukhodim Faridah; Azizah, Nurul (Universitas Muhammadiyah Sidoarjo, 2020)
The postpartum period starts from the birth of the placenta until 6 weeks or is marked by the cessation of bleeding, the postpartum period is considered a critical period because postpartum women must be monitored to detect complications as early as possible during the postpartum period. During the postpartum period, complaints of abdominal pain / after pain often occur which can interfere with the comfort of the postpartum mother. This case study was conducted at PMB Lastakningsih Larangan Sidoarjo which was conducted on January 1, 2020. This midwifery care was carried out by interviewing and obtaining data using the SOAP method. The results obtained from the care of physiological postpartum mothers without complications and there is no gap between theory and practice.